Fermentation of high concentrations of lactose to ethanol by engineered flocculent saccharomyces cerevisiae - Guimarães, Pedro M. R. (2008)
The development of microorganims that efficiently ferment lactose has a high biotechnological interest, particularly for cheese whey bioremediation processes with simultaneous bio-ethanol production. The lactose fermentation performance of a recombinant Saccharomyces cerevisiae flocculent strain was evaluated. The yeast consumed rapidly and completely lactose concentrations up to 150 g l-1 in either well- or micro-aerated batch fermentations. The maximum ethanol titre was 8% (v/v) and the highest ethanol productivity was 1.5–2 g l-1 h-1, in micro-aerated fermentations. The results presented here emphasise that this strain is an interesting alternative for the production of ethanol from lactose-based feedstocks.